"They Pass and Make a Sign": Conrad's Passage on Semiotics - Juhász, Tamás (FOCUS: Papers in English Literary and Cultural Studies, 1998)
In the myth of Narcissus and Echo, Ovid brings together those themes of reflection, substitution and desire that have permeated literary thought for centuries, proved central to Freud and Lacan, and often been the clandestine subject matter of the kind of literature that addresses its own mode of functioning. A turn-of-the-century example is Joseph Conrad’s The Nigger ofthe “Narcissus.” Like the Greek fable, it is also the story of linguistic substitutions, that of a triangular relationship between a main character, his self-image and others. Both technically and psychologically, this is as much the stoiy of the crew as James Wait’s. The same applies to the myth, too, where Echo may technically be seen just as central as Narcissus, where the act of constant displacement, or echoing, is inextricably bound up with the act of complete identity, or reflection. This is an odd duplicity: any narcissistic obsession with one’s mirror image—which, after Lacan, cannot but remain illusory—is both the confirmation of one’s identity as well as its undoing.